Design and development of smart sorting recycle bin prototype - Ismail I.N.B.; Jayakumar P.; Eqwan M.R.; Zuhdi A.W.M.; Mohamad D.; Isa M.R.; Zahari N.M.; Zawawi M.H.; Mohamed H.; Ramli M.Z.; Mansor M.H. (American Institute of Physics Inc., 2023)
Active urbanisation and industrialisation in Malaysia causing massive waste generation. Depleting of landfills is pushing for a new effective approach to solid waste management which is equally important in ensuring the environment is taken care of and free from pollution. Recently the Malaysian government decides to step up in a new holistic approach to a better waste management system where the new implementation of sorting and separation of waste according to a waste composition such as recyclable waste, residual waste and bulky/garden waste at source. This implementation in which requires people to separate their waste and sort the recyclable waste according to categories such as plastic, metal, paper and others. The idea to design and build an automatic waste sorting recycle bin is to support the initiative to separate different kind of trash according to specific categories at the early stage which is at domestic user such as at home and office. This paper discuss the current problem of waste management and how a prototype of smart sorting recycle bin is being developed. 2018 Author(s).